2018
DOI: 10.22438/jeb/39/3/mrn-610
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of growth, yield, tuber quality and profitability of potato upon boron fertilization

Abstract: Aim : Methodology :Results : Interpretation :The study aimed to investigate the effect of soil and foliar boron fertilization on the growth, productivity and quality well as benefit in processing grade potato (Kufri Chipsona-3) in alluvial soil at West Bengal, India.A field experiment was carried out on alluvial soil at West Bengal during the winter season of 2014-15 and 2015-16. The experiment comprised of five treatments [T , Recommended dose of fertilizer (RDF) of NPK; T , RDF of NPK + 2.0 kg soil applied B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…It is clear from these results table (3) that there is a direct relationship occurs between the yield of soft tubers and ascorbic products. These results are consistent with those obtained by [54,59] revealed in their study that the recommended application of NPK and boric acid increased by (0.1) % significantly increased vitamin C (ascorbic acid). The application of molybdenum promoted the growth of vegetable crops and also improved traits such as ascorbic acid [60].…”
Section: Chlorosupporting
confidence: 93%
See 1 more Smart Citation
“…It is clear from these results table (3) that there is a direct relationship occurs between the yield of soft tubers and ascorbic products. These results are consistent with those obtained by [54,59] revealed in their study that the recommended application of NPK and boric acid increased by (0.1) % significantly increased vitamin C (ascorbic acid). The application of molybdenum promoted the growth of vegetable crops and also improved traits such as ascorbic acid [60].…”
Section: Chlorosupporting
confidence: 93%
“…El-Dissoky and Abdel-Kadar (2013) observed the effect of boron foliar application on some potato varieties under sedimentary soil conditions. The boron levels (0, 30, 60 and 90) mg/L -1 showed that foliar application of B significantly affected specific tubular parameters, including [54] in their experience clarify that the recommended application of NPK and boric acid significantly increased protein in potato tubers by (0.1) %.…”
Section: Chloromentioning
confidence: 92%
“…Among all treatments, 180 kg/ha Nitrogen and 50 kg/ha Sulphur showed highest net income and benefit cost ratio. Sarkar et al, (2018) in their experiment revealed that recommended doses of NPK and 0.1% boric acid significantly increases specific gravity, tuber hardness, total soluble solids, total acidity, Vitamin C, protein, and starch content with lowest phenol content. So it is best treatment for producing the processing grade potato.…”
Section: 1% Boric Acidmentioning
confidence: 95%
“…It significantly improved tuber yield, dry matter content, starch content, economic yield and net income. Sarkar et al, (2018) in their experiment revealed that application of boron significantly increased quality characters, namely, specific gravity, TSS, tuber hardness, total acidity and vitamin C content. The lowest phenol content is good for chip colour and it is good for processing industry (Bandana et al, 2016).…”
Section: 1% Boric Acidmentioning
confidence: 97%
See 1 more Smart Citation